Seven wild sisters : a modern fairytale - De Lint, Charles, 1951- (Little, Brown and Company, 2014)
Sarah Jane Dillard discovers and helps an injured fairy in the Tanglewood Forest, putting herself, her six sisters, and friends Aunt Lillian and the Apple Tree Man in the middle of a fairy feud.